If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + -19 = 6y + 11 Reorder the terms: -19 + 4y = 6y + 11 Reorder the terms: -19 + 4y = 11 + 6y Solving -19 + 4y = 11 + 6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6y' to each side of the equation. -19 + 4y + -6y = 11 + 6y + -6y Combine like terms: 4y + -6y = -2y -19 + -2y = 11 + 6y + -6y Combine like terms: 6y + -6y = 0 -19 + -2y = 11 + 0 -19 + -2y = 11 Add '19' to each side of the equation. -19 + 19 + -2y = 11 + 19 Combine like terms: -19 + 19 = 0 0 + -2y = 11 + 19 -2y = 11 + 19 Combine like terms: 11 + 19 = 30 -2y = 30 Divide each side by '-2'. y = -15 Simplifying y = -15
| 4.8-9.6x=12 | | =4d^2-100 | | 4(z-2)=-2(z-5) | | 4(x-5)+3x=7 | | 5x-2=x+7 | | 3x^3-5x^2+2x=0 | | -11=7+6y | | 5.8n+9.17=148.37 | | 7+2(9-3)=-9 | | 28=5n-47 | | =16-8k+k^2 | | 9+3m=45 | | 28x^4+16x^3-80x^2=0 | | 5x-8=x-2 | | 52=4y-12 | | 3(y+1)=9-(y+2) | | 8n-17=87 | | a=1/2(8+4)6 | | 13x+9x+36=-11x-11 | | 6r-7=7-10 | | 5x^2-p-18=0 | | 8x+21-6x+21=-2 | | 2x+7+5x+1= | | 6=-10-p^5 | | (4m+2)+(3-n)i=6-9i | | 7+K=-1 | | 8x^3-12x^2+4x=0 | | 3(5c-1)-3=11c+2 | | y+6y=4-2y | | 4(x-12)+2x+10=0 | | p-4=19 | | 16=m-13 |